2011
DOI: 10.3109/00365521.2011.551891
|View full text |Cite
|
Sign up to set email alerts
|

Association between acid suppressive therapy and spontaneous bacterial peritonitis in cirrhotic patients with ascites

Abstract: PPI use, as well as Child-Pugh class C and high MELD scores, was an independent risk factor for the development of SBP in cirrhotic patients with ascites. Further prospective studies are warranted to clarify this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 20 publications
1
64
1
1
Order By: Relevance
“…Twelve studies were published in journals (Campbell et al, 2008;Bajaj et al, 2009;Choi et al, 2011;Goel et al, 2012;van Vlerken et al, 2012;de Vos et al, 2013;Kwon et al, 2014;Merli et al, 2014;Min et al, 2014;Miura et al, 2014;O'Leary et al, 2014;Ratelle et al, 2014) and 5 studies were reported as conference abstracts (Northup et al, 2008;Bulsiewicz et al, 2009;Aditi et al, 2012;Terg et al, 2012;Mandorfer et al, 2014). We included 8 retrospective cohort studies, 6 case-control studies, and 3 prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies were published in journals (Campbell et al, 2008;Bajaj et al, 2009;Choi et al, 2011;Goel et al, 2012;van Vlerken et al, 2012;de Vos et al, 2013;Kwon et al, 2014;Merli et al, 2014;Min et al, 2014;Miura et al, 2014;O'Leary et al, 2014;Ratelle et al, 2014) and 5 studies were reported as conference abstracts (Northup et al, 2008;Bulsiewicz et al, 2009;Aditi et al, 2012;Terg et al, 2012;Mandorfer et al, 2014). We included 8 retrospective cohort studies, 6 case-control studies, and 3 prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…We could not perform a stratified analysis of duration because of inconsistent definitions. Notably, Choi et al (2011) compared patients who used PPIs for the median duration of time to PPI non-users, deducing that longer duration of PPI use may be associated with an increased risk of SBP. Goel et al (2012) found that patients who had taken PPIs 8 to 90 days before hospitalization for cirrhosis were 79% less likely to develop SBP than those who had taken PPIs within 7 days.…”
Section: Ppi Use and Overall Risk Of Infectionmentioning
confidence: 99%
“…The above study also revealed that 47% of cirrhotic patients receiving PPI had no documented indication for PPI treatment. A recent study on risk factors for bacterial infections among cirrhotics has shown that use of PPI (OR = 3.443, 95% CI 1.164 -10.188; p = 0.025) was a risk factor for SBP [53].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including a meta-analysis [93] of four studies involving a total of 772 patients [94][95][96][97][98] , found significant association between PPI and the development of SBP in patients with cirrhosis (odds ratio 2.77, 95%CI: 1.82-4.23). However, a recent study suggests that even though PPIs may be a contributing factor, the predominant factor determining infection risk is the stage of the liver disease [99] .…”
Section: Secondary Prophylaxis In Patients With Prior Sbpmentioning
confidence: 99%